An Analysis of Illocutionary and Perlocutionary Speech Act in Defamation Texts - Endang Sholihatin (Journal of Languages and Language Teaching, 2020)
The number of defamation in Indonesia keeps increasing. It is proven by many public complaints to the police department. The complaint is mostly about speaker speeches in electronic media. The purpose of this research is to analyze illocutionary and perlocutionary speech act about defamation texts in a family conversation through the social media group. Theoretically, this research has significance in linguistics, especially speech act. Practically it gives a concept and knowledge to society about what kind of speech acts that can insult or defile someone’s good name. The method of this research is qualitative. The data of this research is public complaint texts at the police department in East Java. Based on the analysis, the illocutionary speech act in the family conversation through a social media group includes representative, declarative, and directive. Furthermore, the defamation text in perlocutionary speech act in family conversation through social media group shows that the speakers want their partner to be ashamed in the public.